Penerapan Realistic Mathematics Education (RME) Berbasis Etnomatematika pada Mata Pelajaran Matematika Materi Komposisi dan Dekomposisi Bangun Datar Kelas IV di SDN Dukuh Kupang V Surabaya - Setiyawan, Hery; Amelia, Hikmah Putri; Rivalda, Rizki Nabila; Sudarlin, Yustinus; Damon , Simonsius Aldiano (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the application of the Realistic Mathematics Education (RME) approach based on ethnomathematics in the mathematics subject matter of composition and decomposition of flat shapes for sixth-grade students at Dukuh Kupang V Elementary School in Surabaya. This study uses a qualitative method with a one-shot case study design, conducted in one meeting lasting 2x35 minutes. The research subjects consisted of 21 students, and the data were collected through observations, formative tests, and interviews with the classroom teacher. The research results indicate that group learning using the Realistic Mathematics Education (RME) approach based on ethnomathematics can enhance students' conceptual understanding, with an average group score reaching 93.5. However, when given individual assignments, the average score decreased to 51.4, indicating that group collaboration is more effective in supporting material understanding. Students' responses were generally positive towards this approach, although there were some challenges such as decreased concentration during individual sessions. The integration of Realistic Mathematics Education (RME) and ethnomathematics can improve conceptual understanding if implemented with the right strategies and by considering students' learning dynamics.